The Complete Kotlin Developer Course - Percival, Rob; Walter, Nick (Packt Publishing, 2019)
Use Kotlin instead of Java. Kotlin is a new language that makes programming for Android or JavaScript a dream About This Video Learn Kotlin from the ground up Create two fully functional Android apps In Detail Google is now officially supporting Kotlin in Android development, with the platform recently announcing that it considers the language ideal for Android app developers. Moreover, Kotlin makes it easier to work with JavaScript. In this course, you'll explore a fun and exciting way to learn this language, particularly if you're a beginner. However, experienced programmers will also find this course enriching. If you're just getting started with Kotlin, a dedicated section takes you through Kotlin fundamentals step-by-step. If you already have previous programming experience, you can benefit from the exclusive section titled 'Kotlin for Programmers'. You'll gain hands-on experience by working through projects. The course will guide you through developing two Android apps and a command-line tool. You'll even get to grips with creating JavaScript for a website. While exploring further sections, you'll encounter challenges that will test your new skills and make sure you're getting the most out of this course. By the end of this course, you will be well-versed in Kotlin and have the skills you need to build Android apps, create JavaScript, and much more.